Analyzing the determinants of freight shipper's behavior: own account versus purchased transport - Cristina Borra; Luis Palma (European Regional Science Association (ERSA), 2004)
Previous work in the demand for freight transportation has focused in the rail-truck substitution problem, leaving aside the prior own-account versus third-party trade-off, often found in transportation decision-making. The purpose of this paper is to analyze shippers' behavior relative to this question, paying particular attention to whether the decision to use a private form of transport is taken on a short term or on a medium term horizon. In order to provide a quantitative evaluation, as an illustrative case, the models developed are tested on data gathered by means of a sample survey conducted to Andalusian enterprises belonging to the food industry. JEL classification: R410: Transportation: Supply, Demand and Congestion. C350: Econometric Methods: Multiple/Simultaneous Equation Models: Truncated and Censored Models.
Keywords: 330